2019
DOI: 10.1002/ajmg.a.61365
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 13 and 18—Prevalence and mortality—A multi‐registry population based analysis

Abstract: The aim of the study is to determine the prevalence, outcomes, and survival (among live births [LB]), in pregnancies diagnosed with trisomy 13 (T13) and 18 (T18), by con-genital anomaly register and region. Twenty-four population- and hospital-based birth defects surveillance registers from 18 countries, contributed data on T13 and T18 between 1974 and 2014 using a common data-reporting protocol. The mean total birth prevalence (i.e., LB, stillbirths, and elective termination of pregnancy for fetal anomalies [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 22 publications
(50 reference statements)
4
75
2
1
Order By: Relevance
“…The papers by Meyer et al and Nelson et al documented a more than a doubling of this 1‐year survival for both trisomy 13 and 18 syndromes and that the overwhelming majority of infants who survived to 1 year lived to 5 years. The paper by Goel et al, published in this issue of the Journal demonstrated a similar 1‐year survival in a large‐scale international study of collected data. Overall, about 12% of infants with both conditions survived to the first year of life.…”
mentioning
confidence: 67%
“…The papers by Meyer et al and Nelson et al documented a more than a doubling of this 1‐year survival for both trisomy 13 and 18 syndromes and that the overwhelming majority of infants who survived to 1 year lived to 5 years. The paper by Goel et al, published in this issue of the Journal demonstrated a similar 1‐year survival in a large‐scale international study of collected data. Overall, about 12% of infants with both conditions survived to the first year of life.…”
mentioning
confidence: 67%
“…With the increase in the number of women delaying childbearing and the development of prenatal screening tests such as cell-free fetal DNA technologies, there is a parallel increase in the number T18 prenatal diagnoses [20]. Albeit it is characterized by variable clinical manifestations, with involvement of multiple organs and systems and counting more than 130 different anomalies, which may affect virtually all organs and systems, recent studies seem to encourage the shift from traditional palliative care to therapeutic procedures [8,34,38,39,44], with a parallel increases in survival rates (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…Additional information available in the literature regarding the use of a patient-centered care approach and the impact of surgical interventions on the long-term outcomes were also communicated [2,3,6,8,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Following a painful decision-making process, a final request for therapeutic termination of pregnancy was made.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, live births occur for trisomies of chromosomes 13, 18, 21, X, and Y, owing to the smaller number of genes encoding proteins located on these chromosomes in comparison to the other autosomal chromosomes [14][15][16][17][18]. However, trisomy 13 and trisomy 18 have severe phenotypic consequences, which are rarely compatible with long-term survival [19][20][21][22]. Here, we address genome editing technology as a potential therapy for aneuploidy disorders.…”
Section: Human Genetic Aneuploidy Disordersmentioning
confidence: 99%